2014
DOI: 10.1186/1741-7007-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Division in Escherichia coliis triggered by a size-sensing rather than a timing mechanism

Abstract: BackgroundMany organisms coordinate cell growth and division through size control mechanisms: cells must reach a critical size to trigger a cell cycle event. Bacterial division is often assumed to be controlled in this way, but experimental evidence to support this assumption is still lacking. Theoretical arguments show that size control is required to maintain size homeostasis in the case of exponential growth of individual cells. Nevertheless, if the growth law deviates slightly from exponential for very sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(178 citation statements)
references
References 41 publications
14
163
0
1
Order By: Relevance
“…Cells have to reach a certain critical size at which cell-cycle transitions are triggered, such as G1-S or G2-mitosis (Ivanov, 1971;Dobrochaev and Ivanov, 2001;Dolznig et al, 2004;Yang et al, 2006;Turner et al, 2012;Robert et al, 2014). Therefore, along the PD it is expected that cells are equal to or smaller than the critical size of dividing cells (L critD ).…”
Section: Determination Of the Pd/td Boundary By The Msc Approach Coinmentioning
confidence: 99%
“…Cells have to reach a certain critical size at which cell-cycle transitions are triggered, such as G1-S or G2-mitosis (Ivanov, 1971;Dobrochaev and Ivanov, 2001;Dolznig et al, 2004;Yang et al, 2006;Turner et al, 2012;Robert et al, 2014). Therefore, along the PD it is expected that cells are equal to or smaller than the critical size of dividing cells (L critD ).…”
Section: Determination Of the Pd/td Boundary By The Msc Approach Coinmentioning
confidence: 99%
“…Previous work in other organisms has suggested that there is either a timer or a body size-based trigger for moulting transitions in ecdysozoan growth [13]; this is analogous to 'Timer' versus 'Sizer' models for the proliferation of individual cells [14,15]. For example, the hormone ecdysone has been shown to be a secreted signal important for the timing of larval stage transitions in the moth Manduca sexta.…”
Section: Introductionmentioning
confidence: 99%
“…In each case, to facilitate comparison, 500 cells are plotted (see Methods for details), and their size is plotted versus their rank from smallest to largest. Variation in size is expected, with cells immediately predivision having twice the length (but the same width) as cells immediately post-division (Robert et al, 2014).…”
Section: Effects Of Adomet Analogues On Cell Morphologymentioning
confidence: 99%
“…This allowed calculation of cell areas in the plane of the micrograph. As E. coli cell widths are essentially constant at a given growth rate (Pierucci, 1978;Robert et al, 2014), area is proportional to length. For E. coli strains B/r and MG1655 (K-12) growing in rich media, those studies reported widths of 0.87 and up to 0.95 mm, respectively.…”
mentioning
confidence: 99%